Characteristics of TMD headache -- a systematic review. - Zito G; Morris ME; Selvaratnam P (Physical Therapy Reviews, 2008)
Objective: This systematic review critically evaluated the literature on the subjective and physical characteristics of TMD-related headache, a symptom secondary to the syndrome temporomandibular disorders (TMD). The specific research question is: 'what are the diagnostic criteria that confirm temporomandibular involvement in headache presentations?' Method: Electronic searches were conducted for MEDLINE, PubMed, and CINAHL from 1966 to September 2007. Hand searches for retrieved articles were also conducted to collect the data for this review. After applying inclusion criteria, 15 articles on TMD-related headache were found. Results: The symptoms of TMD-related headache are frequently unilateral and often present in the pre-auricular, temple and retro-orbital regions of the head. The principal physical characteristics include tenderness of the ipsilateral masticatory muscles and reduced jaw opening, often with mandibular deviation. Conclusion: Despite methodological problems such as low subject numbers and poorly documented sampling methods and inclusion criteria, the literature showed that TMD-related headache has identifiable diagnostic characteristics. This information could be used to develop guidelines to assist the identification of headaches which emanate from the temporomandibular structures.